Antifungal films based on starch-gelatin blend, containing essential oils. (December 2016) - Acosta, Sandra; Chiralt, Amparo; Santamarina, Pilar; Rosello, Josefa; González-Martínez, Chelo; Cháfer, Maite
Abstract: The antimicrobial activity of essential oils (EO) is very well-known and it has been reported that incorporating them into edible films based on biopolymers extends the food's shelf-life. In this study, cinnamon, clove and oregano EO, at 25% with respect to the polymer, were incorporated into glycerol plasticized starch-gelatin blend films (ratio 1:1) in order to elucidate their effect on the physical (barrier, mechanical and optical), structural and antifungal properties of the films. Whereas EOs exhibited no significant effect on tensile behavior in the case of casting films conditioned at 53% relative humidity and 25° C, the EO compounds did significantly reduce the water vapor and oxygen permeability of the films. Likewise, the EOs increased the films' transparency but reduced their gloss. Despite the fact that about 60% of the incorporated EOs were lost during the film drying step, they exhibited antifungal activity against the two tested fungal species, Colletotrichum gloesporoides (CG) and Fusarium oxysporum (FOG), as revealed by the in vitro agar diffusion method. Graphical abstract: Highlights: Antifungal films containing cinnamon bark, clove and oregano oils were developed. Essential oils reduced WVP and OP, maintaining mechanical properties of films. Films with cinnamon oil were more effective against Fusarium oxysporum . Films containing clove oil were more effective against Colletotrichum gloesporoides .